2011
DOI: 10.1016/j.apmr.2011.02.015
|View full text |Cite
|
Sign up to set email alerts
|

Sex Differences in Lumbopelvic Movement Patterns During Hip Medial Rotation in People With Chronic Low Back Pain

Abstract: Objective To examine sex differences in lumbopelvic motion and symptom behavior during hip medial rotation in people with low back pain (LBP). We hypothesized that men would demonstrate greater and earlier lumbopelvic motion and would be more likely to report increased symptoms compared to women. Design Cross-sectional observational study. Setting University musculoskeletal analysis laboratory. Participants Thirty men and 29 women with chronic LBP were recruited from the community and a university-based … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 30 publications
(22 citation statements)
references
References 48 publications
1
20
0
1
Order By: Relevance
“…Both men and women decreased their lumbopelvic rotation range of motion and increased the amount of hip rotation completed before the start of lumbopelvic motion. Consistent with previous literature, men demonstrated greater lumbopelvic rotation that began earlier in the range of hip medial rotation compared to women before treatment [26]. Furthermore, results of this study demonstrate that baseline differences remain following treatment.…”
Section: Discussionsupporting
confidence: 90%
“…Both men and women decreased their lumbopelvic rotation range of motion and increased the amount of hip rotation completed before the start of lumbopelvic motion. Consistent with previous literature, men demonstrated greater lumbopelvic rotation that began earlier in the range of hip medial rotation compared to women before treatment [26]. Furthermore, results of this study demonstrate that baseline differences remain following treatment.…”
Section: Discussionsupporting
confidence: 90%
“…The without LBP [59][60][61]. Nevertheless, it was suggested that gender differences may not be relevant when subgrouping subjects by different patterns of lumbar posture and movements [62].…”
Section: Discussionmentioning
confidence: 99%
“…Direction of hip rotation, early lumbopelvic motion, and LBP have gender‐specific associations . In a study of gender differences, Gombatto et al compared LBP symptoms in 27 males and 19 females using three dimensional kinematic assessment of motion during hip external rotation.…”
Section: Secondary Subgroupmentioning
confidence: 99%
“…Direction of hip rotation, early lumbopelvic motion, and LBP have gender-specific associations. 53,73,76,80 In a study of gender differences, Gombatto et al 73 compared LBP symptoms in 27 males and 19 females using three dimensional kinematic assessment of motion during hip external rotation. During the first 60% of hip external rotation, men had a greater percentage of maximum lumbopelvic rotation as compared to women (P < .01).…”
Section: Gender and Lumbopelvic Motion Associated With Hip Motionmentioning
confidence: 99%